5. KERJASAMA INDONESIA DAN UNICEF DALAM MENANGANI KASUS CHILD TRAFFICKING DI INDONESIA PERIODE 2009-2014 - Alfatih, Muhammad Hadziq; Susiatiningsih, Hermini; Hanura, Marten (Journal of International Relations, 2017)
Indonesia has been the country for source, transit, and destination in every forms of human trafficking, including the market which sells childs as the object,known as child trafficking. To solve the case, Indonesia's Government builds a cooperation with UNICEF, international institution which concerns to raise welfare for mothers and childs. This research is aimed to study the cooperation between Indonesia and UNICEF in eradicating child trafficking in Indonesia in 2009-2014. To analyze the cooperation, this research uses liberal institutionalism theory with qualitative method, and explanatory-based research by interviews and literature studies. In this research, we know that the cooperation between Indonesia and UNICEF produces several programs which are expected to help eradicate child trafficking in Indonesia. Those programs are Multiple Indicator Cluster Surveys (MICS) by cooperating with Asian Development Bank (ADB), education programs in East and Central Java for dropout students, PKSA program for homeless childs, and counseling programs to raise awareness about the rights of the child.